Two new phenolic glycosides from the stem of Zanthoxylum armatum DC. Issue 20 (18th October 2017) - Guo, Tao; Dai, Li-Ping; Tang, Xiao-Feng; Song, Tong-Tong; Wang, Ya; Zhao, Ai-Hong; Cao, Ying-Ying; Chang, Jun
Abstract: Two new phenolic glycoside, 2-methoxy-4-hydroxylphenyl-1-O-α-L-rhamnopyranosyl- (1″ → 6′)-β-D-glucopyranoside. (1 ) and threo-3-methoxy-5-hydroxy-phenylpropanetriol-8-O-β-D-glucopyranoside (2 ), were isolated from the stems of Zanthoxylum armatum . The compounds 1 and 2 showed weak scavenging activity in DPPH free radical assay with IC50 values of 323 and 114 mM, respectively. Abstract :